An Analysis of Lexical Cohesion Used by Donald Trump’s Inauguration Speech “The United States will be The First” (2017) - Merry Rullyanti; heni sriwigati (Literary Criticism, 2018)
In this research, the researcher discusses the using of lexical cohesion in inauguration speech by Donald Trump on January, 20, 2017. This research aimed to know kinds of lexical cohesion appear in inauguration text, and also to know the associative meaning used in inauguration speech.The researcher used a descriptive qualitative method in this research and applied Halliday and Hasan’s theory of cohesion to find out the lexical cohesion devices utilized in the speech text. And then, the researcher applied Geoffrey Leech’s theory of types of associative meaning to find out types of associative meaning used in the inauguration speech. Spredley’s domain analysis, taxonomic and componential analysis used for analyzing the data.The result of this research show the lexical cohesion devices utilized in the inauguration speech text are reiteration (repetition, synonym, near synonym, and superordinate) and collocation. While, the associative meaning types utilized in inauguration speech text are connotative meaning, affective meaning, reflected meaning and collocative meaning. Keywords: Donald Trump, Lexical Cohesion, Speech.